Dexter. The seventh season [videorecording (DVD)]. - Vélez, Luna, 1964-; Remar, James; Hall, Michael C., 1971-; Zayas, David; Harrington, Desmond, 1976-; Carpenter, Jennifer, 1979-; Lee, C. S. (Charlie S.), 1971- (Paramount, 2013)
Dexter is forced to confront his greatest fear, as Debra witnesses his insatiable, ritualistic slaying of a killer. Deb knows the secret of his Dark Passenger, his undeniable thirst for blood, and the Code that their father Harry instilled in him as a young boy. But as Deb tries to reconcile the unfathomable idea that her beloved, mild-mannered brother is Miami's most notorious serial killer, Dexter is still pulled by his impulses to seek out the guilty and exact his brand of vigilante justice.